Unilateral hypertrophic skin lesions, hemimegalencephaly, and meningioma: The many faces of Proteus syndrome - Niharika R Lal; Debabrata Bandyopadhyay; Asim K Sarkar (Wolters Kluwer Medknow Publications, 2015)
Proteus syndrome is a rare condition with a wide spectrum of abnormalities. It is characterized by hamartomatous malformations involving multiple organs. Serious complications may ensue, such as pulmonary embolism, cystic lung disease, and various neoplasms such as parotid adenomas, ovarian cystadenomas, and meningiomas. We report here a case of Proteus syndrome in a 21-year-old woman who had facial hemihypertrophy, cerebriform plantar hyperplasia, hemimegalencephaly, and meningioma for the rarity of the entity.